2018
DOI: 10.4055/cios.2018.10.4.393
|View full text |Cite
|
Sign up to set email alerts
|

Remaining Loose Bodies after Arthroscopic Surgery Including Extensive Capsulectomy for Synovial Chondromatosis of the Hip

Abstract: BackgroundThe purpose of our study was to evaluate the usefulness of hip arthroscopy including extensive capsulectomy for synovial chondromatosis of the hip.MethodsFrom 2008 to 2016, 13 patients with synovial chondromatosis of the hip were treated with arthroscopic removal of loose bodies and synovectomy using three arthroscopic portals. An extensive capsulectomy was performed to allow the remaining loose bodies to be out of the extracapsular space, and the excised capsule was not repaired. All patients were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…8 Therefore, we have developed a standardized protocol to maximize the removal of loose bodies and synovium. 25 Applying this technique in the current study, we found that 14 of 23 patients (60.8%) had residual loose bodies, which was lower than 7 of 9 (77.8%) patients reported by Lee et al 12 Most of the residual loose bodies presented at the posterior capsule and posterior acetabular fossa on CT, areas that pose challenges for arthroscopic access. Extended incision of the lateroposterior joint capsule could also cause migration of loose bodies to outside of the joint, such as to the obturator externus and subcutaneous area.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…8 Therefore, we have developed a standardized protocol to maximize the removal of loose bodies and synovium. 25 Applying this technique in the current study, we found that 14 of 23 patients (60.8%) had residual loose bodies, which was lower than 7 of 9 (77.8%) patients reported by Lee et al 12 Most of the residual loose bodies presented at the posterior capsule and posterior acetabular fossa on CT, areas that pose challenges for arthroscopic access. Extended incision of the lateroposterior joint capsule could also cause migration of loose bodies to outside of the joint, such as to the obturator externus and subcutaneous area.…”
Section: Discussioncontrasting
confidence: 40%
“…27 Therefore, concern regarding the necessity of reoperation due to residual loose bodies has been addressed. Lee et al 12 reported that 7 patients with residual loose bodies showed improvement of PROs, including VAS (from 5.4 to 4.0), mHHS (from 80.4 to 90.1), University of California, Los Angeles, score (from 4.4 to 4.8), and Western Ontario and McMaster Universities Osteoarthritis Index score (from 24.2 to 14.6), with no recurrence at a mean follow-up of 3.8 years. However, a control group was not included in their study, which may preclude drawing precise conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study has recommended Magnetic Resonance Imaging (MRI) as a more sensitive diagnostic study than other studies. 8 MRI has the advantage that it can delineate cartilage clearly and can show the cartilaginous bodies which appear as signal voids on all sequences and are sometimes surrounded by bright signal intensity on T2-weighted images. Technetium bone scans through nonspecific can be of some benefit in a few cases.…”
Section: Discussionmentioning
confidence: 99%
“…If the symptoms are not relieved by conservative treatments, surgical intervention is recommended for symptomatic patients with synovial chondromatosis of the hip. 8 Complete synovectomy has been found to reduce the rate of recurrence. 1 Another major concern besides recurrence is the malignant transformation.…”
Section: Discussionmentioning
confidence: 99%